A Document Imaging Technique for Implementing Electronic Loan Approval Process - J. Manikandan; C.S. Celin; V.M. Gayathri (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
The image processing is one of the leading technologies of computer applications. Image processing is a type of signal processing, the input for image processor is an image or video frame and the output will be an image or subset of image [1]. Computer graphics and computer vision process uses an image processing techniques. Image processing systems are used in various environments like medical fields, computer-aided design (CAD), research fields, crime investigation fields and military fields. In this paper, we proposed a document image processing technique, for establishing electronic loan approval process (E-LAP) [2]. Loan approval process has been tedious process, the E-LAP system attempts to reduce the complexity of loan approval process. Customers have to login to fill the loan application form online with all details and submit the form. The loan department then processes the submitted form and then sends an acknowledgement mail via the E-LAP to the requested customer with the details about list of documents required for the loan approval process [3]. The approaching customer can upload the scanned copies of all required documents. All this interaction between customer and bank take place using an E-LAP system.